2022
DOI: 10.3389/fmed.2022.835998
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Sequencing of SARS-CoV-2 Infection in a Cluster of Immunocompromised Children in Indonesia

Abstract: BackgroundThus far, Indonesia has recorded over 4,000,000 confirmed COVID-19 cases and 144,000 fatalities; 12.8% of cases have been in children under 18 years. Whole-genome viral sequencing (WGS) of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been demonstrated to help differentiate hospital-acquired infection from community-acquired coronavirus disease 2019 (COVID-19) infection. Our study highlighted the use of WGS to investigate the origin of infection among pediatric oncology patients in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…However, the most common mutants were found in the Spike‐D614G, N‐R203K, N‐G204R and NSP12‐P323L 8 . Further analysis of SARS‐CoV‐2 sequencing confirmed that multiple mutations in the genome concentrated in the open reading frame area and SPs 9–11 . The most important variants and mutations (https://covariants.org/) regarding viral infectivity were found in SPs at the position of 614 (D614G) (see Figure 1).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, the most common mutants were found in the Spike‐D614G, N‐R203K, N‐G204R and NSP12‐P323L 8 . Further analysis of SARS‐CoV‐2 sequencing confirmed that multiple mutations in the genome concentrated in the open reading frame area and SPs 9–11 . The most important variants and mutations (https://covariants.org/) regarding viral infectivity were found in SPs at the position of 614 (D614G) (see Figure 1).…”
Section: Introductionmentioning
confidence: 97%
“… 8 Further analysis of SARS‐CoV‐2 sequencing confirmed that multiple mutations in the genome concentrated in the open reading frame area and SPs. 9 , 10 , 11 The most important variants and mutations ( https://covariants.org/ ) regarding viral infectivity were found in SPs at the position of 614 (D614G) (see Figure 1 ). As noticed, mutations in receptor binding protein (RBD) of the SPs enhance the stability of the virus structure and infectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Whole-genome sequencing (WGS) of SARS-CoV-2 can guide management of SARS-CoV-2 outbreaks. Several case studies of isolated hospital 12,13 and long-term care facility 14 outbreaks have demonstrated its role in establishing the source of the outbreak, transmission dynamics, and links. The greatest benefit of WGS for SARS-CoV-2 outbreak management accrues when the result is rapidly available (ie, within 5 days).…”
mentioning
confidence: 99%
“…15 Limited access to WGS or reliance on data sharing from centralized models of sequencing for public health greatly influence its utility and the ability to influence infection control responses at a local level. [12][13][14] The objective of this study was to demonstrate the utility of real-time, on-site SARS-CoV-2 WGS.…”
mentioning
confidence: 99%